What Is an Animal? Contagion and Being Human in a Multispecies World - Cole, Lucinda (Lumen, 2021)
From the early modern period to well into the eighteenth century, cattle plagues, murrains, or what were called “great cattle mortalities” were often analogized to bubonic plague; felling animals in devastating numbers, these catastrophes likewise afflicted living creatures on a grand scale. Three Enlightenment cattle pandemics (1709–1720, 1742–1760, and 1768–1786) propelled governments across Europe to enact harsh regulatory measures, including widespread slaughters, quarantines, and major disruptions of trade. This article examines works by Theophilus Lobb, Richard Bradley, Nathaniel Hodges, and Daniel Defoe, among other writers and physicians, who responded differently to the ways in which human and animal health were biophysically and imaginatively linked.